2019
DOI: 10.3390/molecules24091646
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Antioxidant Potential of Selected Dietary Vitamins; Computational Insights

Abstract: Density functional theory (DFT) was used to explore the antioxidant properties of some naturally occurring dietary vitamins, and the reaction enthalpies related to various mechanisms of primary antioxidant action, i.e., hydrogen atom transfer, single electron transfer–proton transfer, and sequential proton loss–electron transfer were discussed in detail. B3LYP, M05-2X, and M06-2X functionals were utilized in this work. For aqueous phase studies, the integral equation formalism polarized continuum model (IEF–PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 21 publications
2
42
1
Order By: Relevance
“…The minimum value appears to be the SMD one. In general, vitamins with higher IP values are more susceptible to ionization and they have stronger antioxidant potential (Pandithavidana and Jayawardana, 2019). Thermodynamics of heterolytic dissociation of chemical bonds can be described using through proton affinity (PA), which is for the anion formation defined as:…”
Section: Resultsmentioning
confidence: 99%
“…The minimum value appears to be the SMD one. In general, vitamins with higher IP values are more susceptible to ionization and they have stronger antioxidant potential (Pandithavidana and Jayawardana, 2019). Thermodynamics of heterolytic dissociation of chemical bonds can be described using through proton affinity (PA), which is for the anion formation defined as:…”
Section: Resultsmentioning
confidence: 99%
“…However, little is known about the radical-scavenging mechanism of PTS. There are three mechanisms for the initial step of the radical-scavenging reaction of phenolic antioxidants: one-step hydrogen-atom transfer (HAT) from the phenolic OH group; electron transfer followed by proton transfer (ET–PT); and sequential proton-loss electron transfer (SPLET) [ 7 ]. Redox-inactive metal ions, such as magnesium ion (Mg 2+ ), are a powerful tool to examine the involvement of electron-transfer processes [ 8 , 9 , 10 , 11 , 12 , 13 ], because it has been reported that electron-transfer reactions are significantly accelerated by their presence [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the principal goals of theoretical chemists is to develop new and useful rules and theories to explain the reactivity properties and to predict the directions and mechanisms of chemical reactions [1][2][3][4][5][6][7][8][9][10]. Density Functional Theory (DFT) that was revealed in accordance with this goal uses the electron density to identify the reactivity or stability [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%